A Comparative Assessment of On-Campus and Off-Campus Students’ Housing in the University of Ibadan, Nigeria (2015)
The University of Ibadan is faced with a persistent challenge of providing adequate students’ housing as a result of explosion in the students’ population in consequence of which the on-and off-campus students’ housing policy was adopted. Existing literature on students’ housing investigated on-campus students’ housing but neglected off-campus students’ housing. This study therefore, conducted a comparative assessment of the on-and off-campus students’ housing in the University of Ibadan, Nigeria. Systems theory provided the analytical framework, while survey research design was employed. A systematic random sampling technique was adopted to select respondents among registered on-and off-campus students. Five percent (A total of 400 on-campus and 700 off-campus students) were randomly selected from the 12 on-campus halls of residence and 22 off-campus hostels respectively. Off-campus hostels were drawn from University of Ibadan adjoining residential neighbourhoods (Agbowo, Orogun, Ajibode, Apete, Samonda and Bodija). A questionnaire containing socio-demographic characteristics, health status indicator (reported cases of illnesses of malaria, cold/catarrh, cholera/diarrhoea and typhoid for the past two weeks at the time of survey), academic performance indicator (Cumulative Grade Point Average [CGPAs] of the 2009/2010 session), distance indicators (punctuality at lectures and time in transit) and social activities indicators (participation in sports, religion, and peer group) were used to elicit information from the students. Observational checklist was used to assess the quality of housing (windows sizes, netting, residential density and airspace). Data were analysed using descriptive and inferential statistics (Chi-square test, t-test and logistic regression) at p≤0.05. Respondents’ age was 24±7years, 75.8% were males. Off-campus students took ill more than their on-campus counterparts (β=-1.8): malaria (off-campus 40.3%; on-campus 23.3%); cold/catarrh (off-campus 18.3%; on-campus 16.7%), cholera/diarrhoea (off-campus 16.7%; on-campus 14.9%) and typhoid (off-campus 15.2%; on-campus 14.9%). On the average, on-campus students had a better academic performance (CGPA=4.2) than off-campus students (CGPA=3.5) with t=8.0. Average waiting time for transportation for off-campus students was between 16-30 minutes compared to on-campus students (1-15 minutes). On-campus students spent an average of 15 minutes in transit while off-campus students spent 59 minutes in transit (X2 =69.8). On-campus students socialise more than off-campus students in sporting activities (β=0.2), religious activities (β=0.1) and peer-group activities (β=0.3). The health of off-campus students was more endangered due to poor window design than their on-campus counterparts with good ventilation; 76.4% of on-campus students have nets in their rooms compared to 31.3% of off-campus students. Residential density was higher in off-campus (83.4%) than on-campus (12.4%) and air space was more adequate in on-campus (86.3%) than off-campus (19.5%). On-campus students’ housing was more conducive for health and learning than off-campus in the University of Ibadan. Therefore, on-campus accommodation should be increased significantly to cater for the student population in the university, while off-campus accommodation providers should be encouraged to improve on their service delivery.